The rupture of the ore slurry pipeline in Santo Antônio do Grama/MG: socio environmentals from the perspective of the national media (Research, Society and Development, 2021)
The mining activity plays a vital role to the economy of a country. However, inherent to its activity, a mining company causes environmental alterations where it is installed. To manage these impacts and assure that mining companies are taking compensatory measures, the government has created a system of environmental licensing. Minas-Rio ore slurry pipeline system, the largest of the world, had a controversial and complicated process of requesting licenses from the Federal Public Ministry. Nevertheless, through political willingness of Minas Gerais and Rio de Janeiro states, obtained approval permits, as well as tax incentive benefits and the public utility title. In 2018, with less than four years of operation, Anglo American mining company, manager of the system, had reported two occurrences of ore slurry pipeline rupture. It spiled 474 tons of iron ore slurry into the Santo Antônio do Grama River. This paper aimed to evaluate the main socio-environmental impacts caused by the rupture of the Minas-Rio ore pipeline from point of view of media. To achieve this, have sought to elucidate the main impacts and the main post-accident news. Research was conducted in the main media of the country, as well as bibliographic search in case studies, thesis and articles. Findings of this study, indicate that socio-environmental impact, arising from the Minas-Rio ore slurry pipeline, is well beyond the rupture episodes occurred in March 2018. Also, the results show that economic power was placed above duties towards the environment.